Strengthening Character Values through High-Quality Islamic Religious Education Learning at Muhammadiyah 8 Junior High School Surakarta in the 2025/2026 Academic Year - Fiki Vendi Muchasin; Sukari (At Turots: Jurnal Pendidikan Islam, 2026)
This study explores the strengthening of character values through high-quality Islamic Religious Education (IRE) learning at Muhammadiyah 8 Junior High School Surakarta in the 2025/2026 academic year. The research aims to analyze how the quality of IRE learning contributes to the development of students’ character values, particularly in fostering religious attitudes, discipline, honesty, and responsibility. Strengthening character education through effective religious instruction is considered essential in responding to moral and social challenges among students in secondary education.The study employed a descriptive qualitative approach supported by quantitative data to obtain a comprehensive understanding of the learning process and its outcomes. The research involved 30 students as participants. Data were collected through classroom observations, questionnaires, in-depth interviews, and documentation. The qualitative data were analyzed using data reduction, data display, and conclusion drawing, while quantitative data were analyzed using descriptive percentage techniques to support the qualitative findings.The results indicate that high-quality IRE learning—implemented through interactive teaching methods, contextual learning materials, exemplary teacher behavior, and continuous evaluation—effectively strengthens students’ character values. The findings show that 83% of students experienced an improvement in religious attitudes, 80% demonstrated increased discipline, 76% showed stronger honesty, and 78% exhibited enhanced responsibility in their daily school activities. These results suggest that the implementation of quality-oriented Islamic Religious Education plays a significant role in reinforcing students’ character formation and can be categorized as effective in supporting character education at the junior high school level